Correlation study of CYP2C19 gene polymorphism and clopidogrel resistance in Han Chinese patients with cerebral infarction in Guizhou region. Issue 6 (12th February 2021) - Shi, Guo-Xian; Zhao, Zi-He; Yang, Xiao-Yan; Lin, Mu; Chen, Zhou-Xue
Abstract : Abstract: This study conducts a correlation exploration of CYP2C19 gene polymorphism and clopidogrel resistance in Han Chinese patients with cerebral infarction in Guizhou Region. A total of 270 Han Chinese patients with cerebral infarction, who were hospitalized in our hospital from January 2016 to January 2018, are selected. These patients were divided into 2 groups, clopidogrel resistance group (n = 60) and clopidogrel sensitive group (n = 210). According to the TEG results, the CYP2C19 gene polymorphism detection was carried out by using the PCR-RFLP method, while IL-6 level in the patient's blood was measured by using the ELISA method. The resistance group occupies 22.22%. The platelet inhibition ratio of the resistance group was 23 ± 7%, which was significantly lower than that of the sensitive group (65 ± 13%), and the difference was statistically significant ( P  < .05). The Logisitic regression analysis revealed that the history of diabetes, history of high blood pressure, increase in low density lipoprotein and CYP2C19 mutant gene were independent risk factors of clopidogrel resistance. After treatment, the serum IL-6 level of patients in the resistance group was 17.21 ± 0.98 ng/L, which was significant higher than that of patients in the sensitive group (11.21 ± 0.68 ng/L), and the difference was statistically significant ( P  < .05). Patients with cerebral infarction in Guizhou region have a higher occurrence rate of clopidogrel resistance. Clopidogrel resistance not only will weaken the anti-inflammatory action of the drug, but also correlates with the patient's CYP2C19 mutant gene and blood lipid level.